Real-world data on efficacy and safety of first-line alectinib treatment in advanced-stage, ALK-positive non-small-cell lung cancer patients: a Turkish Oncology Group study - Hizal, Mutlu; Bilgin, Burak; Paksoy, Nail; Kilickap, Saadettin; Atci, Muhammed Mustafa; Kahraman, Seda; Nahit Sendur, Mehmet Ali (Taylor & Francis Ltd, 2022)
Plain language summary The advancements in cancer treatment, particularly in the last two decades, have been promising. Non-small-cell lung cancer (NSCLC) is one of the most important diseases experiencing these promising developments. ALK positivity, which is caused by the rearrangement of different gene fragments between two chromosomes, affects about 5% of NSCLC patients. This provides a target for next-generation therapies. One of these targeted therapy drugs is alectinib. The authors examined the outcomes of 271 patients with body-disseminated NSCLC who received alectinib as initial targeted therapy. These patients were not chosen to participate in a clinical phase study. They were treated with an approved drug; the study also included 97 patients who had previously received chemotherapy. The median duration of survival without disease worsening was 26 months for all patients receiving alectinib treatment. This value was 28.8 months in 177 patients who had not received any treatment before alectinib. Regardless of disease status, 77% of all patients were found to be alive at the end of the first year. Alectinib treatment resulted in a significant improvement of the disease in approximately four out of five patients. The treatment's side effects were generally tolerable or manageable. Only four patients were reported to have discontinued their medication due to treatment-related side effects. These real-world findings are compatible with previous clinical research. Alectinib is an important first-line treatment option for patients with advanced, ALK-positive NSCLC. Aims: In this multicenter study, the authors aimed to determine the real-life efficacy and safety of first-line alectinib. Materials & methods: This retrospective trial included advanced-stage, ALK-positive non-small-cell lung cancer patients who were treated with first-line alectinib in terms of ALK-tyrosine kinase inhibitors, regardless of previous chemotherapy. The co-primary end points were progression-free survival both for all patients and for the treatment-naive population. The secondary end points were overall response rate, overall survival, rate of CNS progression and safety. Results & conclusion: A total of 274 patients (n = 177 for treatment-naive patients) were enrolled in the study. The median progression-free survival was 26 and 28.8 months for all patients and the treatment-naive group, respectively. The overall response rate, CNS progression rate and 1-year overall survival ratio were 77.9, 12.4 and 77%. Alectinib is a highly effective therapy with a favorable safety profile.
Keywords: alectinib; ALK; first-line; non-small-cell lung cancer; real-world